Development of laser‐based remote sensing technique for detecting defects of concrete lining. Issue 6 (18th April 2019) - Shimada, Yoshinori; Kotyaev, Oleg; Kurahashi, Shinri; Yasuda, Naotoshi; Misaki, Norikazu; Takayama, Yoshihisa; Soga, Toshitaka
Abstract: Laser‐based remote sensing system (LRSS) for detecting defects of concrete lining has been developed. This system can move a central passage in Shin‐kansen tunnel and detected the concrete defects. We have developed automatic positioning and focusing system of impact and detection lasers. It was confirmed that this system inspected concrete defects with remote and high speed and soundness could be judged.